ABSORBING DEVICE WITH VARIABLE MASS OF THE WORKING FLUID - Manashkin, L. O.; Myamlin, S. V. (Science and Transport Progress, 2005)
A mathematical model of a draft gear for rail vehicles is suggested in the paper. Taking into consideration the temperature and other physical phenomena, which take place in the hydro-gaseous draft gears, is a basic peculiarity of the mathematical model.